STYLIZATION OF THE EPIC “GARIB ASHIQ” IN DRAMA - Zhambulova, Raykhan Abdiraziyevna (SCIENCE and SOCIETY, 2026)
The article discusses the staging of the folk epic “Ǵarib oshiq”. The stylization of the epic into a dramaturgical genre and the interrelation of the characters in it, as well as the playwright`s method of creating appropriate images for the stage, are studied.